Case series of elderly patients with scabies topically applied with ivermectin via whole‐body bathing. Issue 4 (6th January 2021) - Komoda, Masayo; Miyajima, Atsushi; Koshino, Machi; Akutsu, Shunta; Yamada, Mizuki; Ozeki, Rie; Makigami, Kuniko
Abstract: As a novel method of ivermectin (IVM) administration for the treatment of scabies, we devised a whole‐body bathing (WBB), in which patients are immersed in a fluid that contains IVM. A multi‐institutional trial for elderly patients with scabies was conducted to investigate the efficacy and safety of IVM‐WBB. Seven elderly patients with scabies were enrolled and received IVM‐WBB up to four times at 1‐week interval. The cure for scabies was defined as the absence of mites in two consecutive microscopic or dermoscopic examinations at weekly intervals and the absence of new skin lesions indicative of scabies. Consequently, the cure rate on day 22, the primary end‐point, was 71.4%, and all patients had been cured until day 29. Additionally, neither significant adverse events nor clinically problematic abnormal blood test values were obtained. Furthermore, no IVM was detected in the optional plasma (five cases) collected for IVM measurement after bathing. These results suggest that IVM‐WBB was effective to treat scabies, causing no serious adverse events and with a very low internal exposure of IVM.